Association of left ventricular size with regional right ventricular mechanics in Hypoplastic Left Heart Syndrome. (1st January 2020) - Forsha, Daniel; Li, Ling; Joseph, Navya; Kutty, Shelby; Friedberg, Mark K.
Abstract: Background: In Hypoplastic Left Heart Syndrome (HLHS), RV dysfunction is associated with poor outcomes. However, the effect of varying LV size on regional RV mechanics and outcome has not been studied. Methods: Twenty newborns (0–7 days) with HLHS had pre-stage 1 and pre-stage 2 echocardiograms prospectively protocoled for strain analysis of the apical 4-chamber view. RV longitudinal strain was analyzed, and LV size was classified as diminutive (no visible LV chamber) or moderate size (visible LV chamber). Clinical outcome was reported as alive vs death or transplant (D-TP) at final clinical follow-up (pre-stage 3). Groups were compared with t -test, Fisher's Exact, and ANOVA tests as appropriate. Results: At pre-stage 1, infants with a diminutive LV (7/20, 35%) vs a moderately hypoplastic LV (13/20, 65%) did not have significantly different global RV strain (−18.4 ± 2.6% vs −18.8 ± 3.2%; p = 0.83). However, basal septal strain was significantly diminished in the moderately hypoplastic LV group vs the diminutive LV group (−4.4 ± 6.0% vs −14.7 ± 3.3%; p < 0.005). There was severely diminished septal strain in nearly all (11/13) of the moderately hypoplastic group. At the pre-stage II echo, global RV strain between groups remained similar ( p = 0.76) as did the diminished septal strain in the moderate LV group ( p = 0.86). The moderately hypoplastic LV group had worse clinical outcomes (6/13 D-TP vs 0/7 D-TP; p = 0.05). Conclusions: In this small HLHS cohort, diminished septal strain leading to asymmetric RV mechanics may be associated with poor outcomes in those with larger LV/septal size. Highlights: RV function is correlated with clinical outcome in Hypoplastic Left Heart Syndrome. Septal contractility of the RV is diminished in those with larger dysplastic LVs. Clinical outcomes were worse in those with larger LV size and poor septal contractility.